CAUSES OF SUICIDAL BEHAVIOUR AS PERCEIVED BY UNDERGRADUATES IN KWARA STATE: IMPLICATIONS FOR VALUE RE-ORIENTATION COUNSELLING - OLUGBON, Saheed, B.; BOLU-STEVE, Foluke N.; MUHAMMED, Shuaib A.; ALAWAYE, Aminullahi, S. (Journal of Professional Counselling, 2025)
This study aimed to investigate whether there is any significant difference in the causes of suicidal behaviour as perceived by undergraduates based on gender, religion, and place of residence. One research question was raised, and three research hypotheses were formulated to guide the study. Adopting a descriptive survey method, the study targeted a population of 104,632 undergraduates in Kwara State. A sample size of 402 respondents was selected through a multistage sampling procedure, but only 394 properly filled forms were analysed. Data were collected using a 15-item closed-ended adapted questionnaire titled "Causes of Suicidal Behaviour Questionnaire" (CSBQ), which had a reliability coefficient of 0.74. Frequency count and percentage were used to analyse demographic data, while mean and rank order were employed for the research question. Hypotheses 1 and 3 were tested using an independent t-test, while hypothesis 2 was analysed using Analysis of Variance (ANOVA). All hypotheses were tested at a 0.05 level of significance.The findings revealed that undergraduates perceived that unstable emotions, family conflict, financial problems, academic pressure, severe sexual harassment or rape among others were causes of suicidal behaviour. The findings of the hypotheses showed that there were significant differences in the causes of suicidal behaviour as perceived by undergraduates based on religion and place of residence, but no significant difference was found based on gender. it was recommended that universities Journal of Professional Counselling, Vol. 8, No. 2 139 managements should organise value re-orientation programmes across all university types, focusing on the identified causes of suicidal behaviour. Counsellors' Associations should train University counsellors on how to organise a sensitive value re-orientation programmee for university students and develop targeted interventions to curb the menace of the various causes identified by undergraduates, such as unstable emotions, family conflict, financial problems, academic pressure, and severe sexual harassment or rape among others that could help reduce suicide risk.